Assessment of current follow‐up for complete molar pregnancies: A single centre review. (8th October 2020) - Mylvaganam, Gaithri; Allanson, Emma; Allanson, Ben; Philp, Shannon; Pather, Selvan; Farrell, Rhonda; Carter, Jonathan; Tejada‐Berges, Trevor
Abstract : Background: Current guidelines recommend that resolution of a complete molar pregnancy (CMP) can only be confirmed once a negative β‐human chorionic gonadotropin (β‐hCG) has been maintained for six months following uterine surgical evacuation. However, multiple studies have found that the risk of developing gestational trophoblastic neoplasia (GTN) once a negative β‐hCG had been obtained is negligible, which suggests that a shorter follow‐up may be reasonable. Aim: To determine the trend in β‐hCG following diagnosis of a CMP and the incidence of GTN, in a single unit. Materials and Methods: All patients presenting to the tertiary hospital, Royal Prince Alfred Hospital Early Pregnancy Assessment Service (RPAH EPAS), with a histopathological diagnosis of a CMP between 2010 and 2017 were included. Data collected included age, parity, β‐hCG at diagnosis, subsequent β‐hCG levels, incidence of GTN and treatment required. Results: Sixty‐seven patients were diagnosed with CMP between January 2010 and July 2017 through RPAH EPAS. The mean age of women diagnosed with a CMP was 33 years. None of the 40 patients who spontaneously achieved a negative β‐hCG and completed their six months follow‐up had a subsequent rise in β‐hCG. The median number of days from surgical evacuation to normalisation of β‐hCG was 55.5 days. Sixteen out of 67 patients who had a CMP required further management for persistent GTN. None of these patients achieved a negative β‐hCG prior to further management. Conclusions: Consideration could be made to decreasing the period of β‐hCG monitoring for women who achieve a spontaneous negative β‐hCG following surgical evacuation of a CMP.